Pandemic Covid-19: Android Application "Mh Mobile" Is A Solution For Leprosy Patients (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Leprosy has not disappeared; this old disease still exists today in our country. Eliminating leprosy requires extra effort, one of which is using technology. Human activity in modern times uses technology. One of the technologies that everyone has is a smartphone. The challenge during a pandemic condition is that it is very risky for people with leprosy if they have to go to a community health center or hospital.  This research was conducted with a quasi-experimental design with a pre-post control group design with a sample size of 70 people. The intervention was carried out using the media in the form of the android application "MH Mobile" in the treatment group. Change in Knowledge and adherence as measured by a validated questionnaire. The questionnaire was measured before and after the intervention and then tested using the Wilcoxon and Mann-Whitney tests.  Statistical analysis showed that there was an effect of MH Mobile on knowledge and adherence (p = 0.000). There were significant changes in the two groups between before and after the intervention. The MH Mobile android application can be an effective means of providing education about leprosy as an effort to increase knowledge during the pandemic era 19